Peptide Gelators to Template Inorganic Nanoparticle Formation - Ottavia Bellotto; Maria C. Cringoli; Siglinda Perathoner; Paolo Fornasiero; Silvia Marchesan (Gels, 2021)
The use of peptides to template inorganic nanoparticle formation has attracted great interest as a green route to advance structures with innovative physicochemical properties for a variety of applications that range from biomedicine and sensing, to catalysis. In particular, short-peptide gelators offer the advantage of providing dynamic supramolecular environments for the templating effect on the formation of inorganic nanoparticles directly in the resulting gels, and ideally without using further reductants or chemical reagents. This mini-review describes the recent progress in the field to outline future research directions towards dynamic functional materials that exploit the synergy between supramolecular chemistry, nanoscience, and the interface between organic and inorganic components for advanced performance.